If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 4)(y + 6) = -4(5y + 4) Reorder the terms: (4 + 5y)(y + 6) = -4(5y + 4) Reorder the terms: (4 + 5y)(6 + y) = -4(5y + 4) Multiply (4 + 5y) * (6 + y) (4(6 + y) + 5y * (6 + y)) = -4(5y + 4) ((6 * 4 + y * 4) + 5y * (6 + y)) = -4(5y + 4) ((24 + 4y) + 5y * (6 + y)) = -4(5y + 4) (24 + 4y + (6 * 5y + y * 5y)) = -4(5y + 4) (24 + 4y + (30y + 5y2)) = -4(5y + 4) Combine like terms: 4y + 30y = 34y (24 + 34y + 5y2) = -4(5y + 4) Reorder the terms: 24 + 34y + 5y2 = -4(4 + 5y) 24 + 34y + 5y2 = (4 * -4 + 5y * -4) 24 + 34y + 5y2 = (-16 + -20y) Solving 24 + 34y + 5y2 = -16 + -20y Solving for variable 'y'. Reorder the terms: 24 + 16 + 34y + 20y + 5y2 = -16 + -20y + 16 + 20y Combine like terms: 24 + 16 = 40 40 + 34y + 20y + 5y2 = -16 + -20y + 16 + 20y Combine like terms: 34y + 20y = 54y 40 + 54y + 5y2 = -16 + -20y + 16 + 20y Reorder the terms: 40 + 54y + 5y2 = -16 + 16 + -20y + 20y Combine like terms: -16 + 16 = 0 40 + 54y + 5y2 = 0 + -20y + 20y 40 + 54y + 5y2 = -20y + 20y Combine like terms: -20y + 20y = 0 40 + 54y + 5y2 = 0 Factor a trinomial. (10 + y)(4 + 5y) = 0Subproblem 1
Set the factor '(10 + y)' equal to zero and attempt to solve: Simplifying 10 + y = 0 Solving 10 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + y = 0 + -10 y = 0 + -10 Combine like terms: 0 + -10 = -10 y = -10 Simplifying y = -10Subproblem 2
Set the factor '(4 + 5y)' equal to zero and attempt to solve: Simplifying 4 + 5y = 0 Solving 4 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5y = 0 + -4 5y = 0 + -4 Combine like terms: 0 + -4 = -4 5y = -4 Divide each side by '5'. y = -0.8 Simplifying y = -0.8Solution
y = {-10, -0.8}
| -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 | | 6x^2+3=5x | | x^2-10x-18=0 | | 3(2x+3)+4=-59 | | 8x-2y=-44 | | 12+(x+3)-3x=117 | | 3(2x+3)+4x=-59 | | c(q)+6000+10qR(q)=12 | | x*x-4=240 | | -84=-15w+9w | | 8(x+2)-2x=4 | | 12x-10-x-4=3 |